2018
DOI: 10.3233/jad-170799
|View full text |Cite
|
Sign up to set email alerts
|

A Selection of Important Genes and Their Correlated Behavior in Alzheimer’s Disease

Abstract: In 2017, approximately 5 million Americans were living with Alzheimer’s disease (AD), and it is estimated that by 2050 this number could increase to 16 million. In this study, we apply mathematical optimization to approach microarray analysis to detect differentially expressed genes and determine the most correlated structure among their expression changes. The analysis of GSE4757 microarray dataset, which compares expression between AD neurons without neurofibrillary tangles (controls) and with neurofibrillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 88 publications
(77 reference statements)
0
19
0
Order By: Relevance
“…In US, there were approximately five million AD cases in 2017, and this number of AD cases is predicted to rise to 16 million by 2050. It is estimated that 1 out of 85 people worldwide would be diagnosed with AD by 2050 [24,25]. Patients with AD experience a slow but gradual decline in memory, thinking, and reasoning skills, with the accompanying dementia that gradually increases in severity, leading eventually to the patient's death.…”
Section: Polyphenols In Alzheimer's Diseasementioning
confidence: 99%
“…In US, there were approximately five million AD cases in 2017, and this number of AD cases is predicted to rise to 16 million by 2050. It is estimated that 1 out of 85 people worldwide would be diagnosed with AD by 2050 [24,25]. Patients with AD experience a slow but gradual decline in memory, thinking, and reasoning skills, with the accompanying dementia that gradually increases in severity, leading eventually to the patient's death.…”
Section: Polyphenols In Alzheimer's Diseasementioning
confidence: 99%
“…It has been shown to be related to inflammatory immune responses and DNA damage ( Markkanen et al ., 2016 ; Howes and McCutcheon, 2017 ; Watkins and Andrews, 2016 ). Nucks1 is a vertebrate-specific gene ( Bai et al ., 2017 ) that has been indicated that the response to DNA damage by HR is important and plays a role in inflammatory immune response ( Cruz-Rivera et al ., 2018 ). It has been shown that nucks1 is related to several nervous system diseases, including BD ( Fries et al ., 2017 ), AD ( Cruz-Rivera et al ., 2018 ) and PD ( Zhu et al ., 2018 , Liu et al ., 2011 , Vacic et al ., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nucks1 is a vertebrate-specific gene ( Bai et al ., 2017 ) that has been indicated that the response to DNA damage by HR is important and plays a role in inflammatory immune response ( Cruz-Rivera et al ., 2018 ). It has been shown that nucks1 is related to several nervous system diseases, including BD ( Fries et al ., 2017 ), AD ( Cruz-Rivera et al ., 2018 ) and PD ( Zhu et al ., 2018 , Liu et al ., 2011 , Vacic et al ., 2014 ). To date, the association between the nucks1 gene and schizophrenia has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Irrespective of their essential roles in ribosome assembly and protein translation, multiple ribosomal proteins possess extraribosomal functions that are closely related to tumor initiation, inflammatory response, and neurodegenerative diseases (Cruz‐Rivera et al, 2018; Doherty et al, 2010; Zhou et al, 2015). Rpl41 has been identified as a tumor suppressor gene, and its deficiency, downregulation, or mutations have been detected in tumors (A. Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%